HIDROPONIK PINTAR MENGGUNAKAN INTERNET OF THINGS UNTUK PEMANTAUAN DAN KENDALI KEBUTUHAN NUTRISI SAYURAN PAKCOY - Pramudya, Jefri (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 1 No 01 (2021): September 2021DO - 10.32503/ammer.v1i01.1880, 2021)
The development of technology is so fast, it encourages the emergence of innovation in agriculture. One of them is innovation in agriculture with a hydroponic system. Hydroponics is an agricultural system with nutrient water as the main component in this system. In conventional hydroponic farming, monitoring and controlling nutrition is still done manually by checking and adding nutrients by humans. To facilitate human work, a monitoring and control system is needed by utilizing the Internet of Things. Making this system using the Blynk application and webserver database connected to the tool made. The results obtained from this system are nutrition monitoring in real time equipped with sensor data storage and control of the nutritional needs of pakcoy vegetables from the first week to the week of harvest.